PENGARUH KEPUTUSAN INVESTASI, PENDANAAN, KEBIJAKAN DIVIDEN DAN SUKU BUNGA TERHADAP NILAI PERUSAHAAN - Ningrum, Frista Cahya; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
Optimizing firm value can be achieved by using management function, in this case the manager should beable to increase the welfare of shareholders which is the company objectives. The firm value is an investorperception to the company which is often associated with stock price. This research is aimed to find out theinfluence of investment decision, financing decision, dividend policy and interest rates to the firm value. Thepopulation in this research is 142 companies which are listed in Indonesia Stock Exchange (IDX) in 2010-2015periods. This research has been done by using purposive sampling technique, and 30 companies have beenselected as samples. The data has been obtained from the Indonesia Stock Exchange (IDX). This research hasbeen carried out by using multiple linear regressions analysis and the SPSS (Statistical Product and ServiceSolutions) software. The result of the research shows that investment decision gives positive influence to the firmvalue, the funding decision gives positive influence to the firm value, dividend policy give positive influence tothe firm value and the interest rate does not give any influence to the firm value.Keywords: investment decision, financing decision, dividend policy, interest rates, firm value.